Asymmetric Deoxygenative Cyanation of Benzyl Alcohols Enabled by Synergistic Photoredox and Copper Catalysis†. Issue 12 (29th October 2020) - Chen, Hong‐Wei; Lu, Fu‐Dong; Cheng, Ying; Jia, Yue; Lu, Liang‐Qiu; Xiao, Wen‐Jing
Abstract : Summary of main observation and conclusion An enantioselective deoxygenative cyanation of benzyl alcohols was accomplished for the first time through the synergistic photoredox and copper catalysis. This reaction features the use of organic photosensitizer and low‐cost 3d metal catalyst, simple and safe operations, and extremely mild conditions. A variety of chiral benzyl nitriles were produced in generally good yields and high level of enantiocontrols from readily available feedstocks (22 examples, up to 93% yield and 92% ee). Abstract : An enantioselective deoxygenative cyanation of benzyl alcohols has been accomplished through synergistic copper/photoredox catalysis. This reaction provides an efficient approach to a variety of chiral benzyl nitriles in high yields and enantioselectivities under mild conditions.